Typical Bengkulu Rafflesia Flower Pattern in Waistbag Design - christy aryani, willia; Indra Gunara Rochyat (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
The purpose of this research is to describe the process of making the Rafflesia Arnoldii flower pattern decoration and to find out the finished results of applying the Rafflesia Arnoldii flower pattern decoration on the waistbag and highlighting the characteristics of Bengkulu. The theme of the creation of this work of art is the Rafflesia Arnoldii flower pattern because it has a visually stunning shape that makes it unique from other flowers. It has an attraction, most people like this flower because of its shape, size and unique way of life. Lives in the tropical rainforests of Sumatra; Therefore, Bengkulu Province is nicknamed